Modeling of a brick building of high storeys on a pile foundation - I. I. Podshivalov; A. V. Zhuravlev (Вестник СибАДИ, 2020)
Relevance. This work is devoted to modeling the stress-strain state of a high-rise brick building on a pile foundation in engineering and geological conditions using the MicroFe design and computing complex, which allows you to create a design scheme in the “base – foundation – building” system using piles in the form of rod end. elements in the soil mass.Goal. Analyzed-deformed state of the system “base – foundation – building”, obtaining the calculated values of tension and reinforcement in the grillage.Materials and methods. The calculation was carried out both in a linear formulation and in a constructively nonlinear formulation with one-sided nonlinear connections between bulk soil elements and pile bar elements. Results. In a nonlinear formulation of the solution to the problem, with a limitation of the permissible design load on the piles, a redistribution of efforts between the piles through the grillage is obtained. Conclusions. Linear calculation is carried out in the case when the greatest forces in the piles do not exceed the specified design load. If this condition is not met, then in the design model, a limitation is introduced on the value of the ultimate load on the piles, equal to the design value, and the calculation is performed considering the constructive nonlinearity of one-sided connections between the pile bar elements and bulk soil elements. Solving the problem in a non-linear formulation allows us to consider the redistribution of efforts between the piles through the grillage, because of which, by changing the location of the piles, it is possible to obtain an optimal design solution for both the pile foundation and the overhead part of the building.